GUIDE AGAINST ELDERLY ABUSE AMONG THE EFIK PEOPLE OF SOUTH-SOUTH, NIGERIA: AN EXAMINATION OF EXODUS 20:12 - Ekpenyong Nyong, Akpanika (Universitas Negeri Makassar, 2020)
Elderly abuse is an issue that has not been given much attention particularly among the Efik speaking people of South-South, Nigeria. The unjust and abusive treatment given generally to the elderly is gradually on the increase in the 21st century. The growing number of parents experiencing abuse, violence and insult in contemporary Efik society by caregivers or sometimes their children desire some attention. Today, since most elderly persons are not seen as breadwinners of the family, they are regarded as not being important and as such, not given the same respect as they deserve. This paper examines the biblical injunction of Exodus 20:12 to honour one's father and mother and its implication among the Efik People of South-South, Nigeria. God through Moses gave the children of Israel some moral laws that guided their relationship with the aged and elderly. The commandment in Exodus 20:12 to honour one's father and mother were primarily to protect them from abuse and neglect. Similarly, among the Efik people, some moral laws protected the aged and the elderly from possible abuse. This obligatory respect for the aged which was a panacea for family stability in the patriarchal period and Efik traditional setting is gradually losing its relevance in contemporary times. This cultural shift calls for reinvigoration in an attempt to stop elderly abuse among the Efik people. The paper adopted the qualitative research method using the hermeneutical and historical approach and discovered that globalization, urbanization and poverty have contributed in no small measure to the devaluing respect that the Efik people had for the aged and recommends the introduction of gerontology as part of civic education in Primary and Secondary schools to recapture these values.